Manufacture of Nickel Collimator for BNCT: Smelting of Nickel Using Electrical Arc Furnace and Centrifugal Casting Preparation - Mujiyono Mujiyono; Suharto Suharto; Alaya Fadllu Hadi Mukhammad; Didik Nurhadiyanto; Arianto Leman Sumowidagdo (Indonesian Journal of Physics and Nuclear Applications, 2018)
Collimator is a tube that functions to direct neutrons generated by a nuclear reactor for BNCT (Boron Neutron Capture Therapy Cancer). Appropriate design of the collimator for BNCT application is a tube with an inner diameter of 16 cm, an outer diameter of 19 cm and a length of 13 cm total with 12 pieces with nickel purity above 95%. Manufacturing of the BNCT collimator will be planned using centrifugal casting method and smelting of nickel with electrical arc (EA) furnace. This article reports on the smelting process of nickel, setting the parameters of the electrical arc furnace, and the chemical composition of the nickel. Results of the study show that nickel with purity 98% can be melted perfectly using the EA Furnace with a current of 600-800 A and a pouring temperature of 1600°C. The fluidity of nickel can hold up to 1 minute at a 35°C environment that allows for the centrifugal casting process. The chemical composition of the nickel before being melted is Ni (98.89%), Si (0.79%), S (0.17%), and Fe (0.15%) and after being melted is Ni (97.89%), Si (0.92%), S (0.26%), and Fe (0.90%). The chemical composition of the nickel after smelting in an EA Furnace meets the requirements of BNCT collimator.